Primary Umbilical Endometriosis: Report of a Rare Case - Bhowmik, Dilip K.; Mirza, Rezwana; Hossain, Amzad (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Endometriosis is the commonest gynaecological problem; it affects 7 to 10% women in reproductive age group. Commonest site being the pelvic organs, extrapelvic presentation in almost all parts of the body have been reported. However umbilical endometriosis has been reported in more than one hundred cases. It was first described by Villar in 1886. Umbilical endometriosis accounts for only 0.5% to 1% of all endometriosis cases. Most of the reported cases occurred in the scar following gynaecological and obstetrical surgery. A few cases of primary umbilical endometriosis have been reported. We report such a rare case of primary umbilical endometriosis and the diagnosis was done by FNAC & the patient underwent wide local excision. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i1.19426